Disruption of Aneuploidy and Senescence induced by Aurora inhibition promotes intrinsic Apoptosis in double hit or double expresser Diffuse Large B-cell Lymphomas - Islam, Shariful (Mol Cancer Ther, 2017)
Double Hit (DH) or Double Expresser (DE) diffuse large B-cell lymphoma (DLBCL) are aggressive Non-Hodgkin’s Lymphomas (NHLs) with translocations and/or over-expression of MYC and BCL-2, that are difficult to treat. Aurora kinase (AK) inhibition with alisertib in DH/DE-DLBCL induces cell death in ~30%, while ~70% are aneuploid and senescent cells (AASCs), a mitotic escape mechanism contributing to drug resistance. These AASCs elaborated a high metabolic rate by increased AKT/mTOR and ERK/MAPK activity via BTK signaling through the chronic active B-cell receptor (BCR) pathway. Combinations of alisertib + ibrutinib or alisertib + ibrutinib + rituximab significantly reduced AASCs with enhanced intrinsic cell death. Inhibition of AK + BTK reduced phosphorylation of AKT/mTOR and ERK-1/2, up-regulated phospho-H2A-X and Chk-2 (DNA damage), reduced Bcl-6 and decreased Bcl-2 and Bcl-xL and induction of apoptosis by PARP cleavage. In a DH/DE-DLBCL SCID mouse xenograft model ibrutinib alone was inactive, while alisertib + ibrutinib was additive with a tumor growth inhibition (TGI) rate of ~25%. However, TGI for ibrutinib + rituximab was ~50–60%. In contrast, triple therapy showed a TGI rate of >90%. Kaplan-Meier survival analysis showed 67% of mice were alive at day-89 with triple therapy versus 20% with ibrutinib + rituximab. All treatments were well tolerated with no changes in body weights. A novel triple therapy consisting of alisertib + ibrutinib + rituximab inhibits AASCs induced by AK inhibition in DH/DE-DLBCL leading to a significant anti-proliferative signal, enhanced intrinsic apoptosis and may be of therapeutic potential in these lymphomas.